SEMIOTICS STUDY ON ASEI BARK PAINTING PATTERNS - Shabiriani, Uzda Nabila (Jurnal Bahasa Rupa, 2022)
There are meanings, stories and philosophies of the life of the ancestors of the Asei people which have been depicted on the bark for generations since 1600 and produce images related to the living space of the Asei people. The purpose of this study was to determine the meaning of the symbolic forms that exist in the Asei bark painting motifs related to the life of the Asei people and their social system. This study analyzes the colors that are often used and the dominance of images in Asei bark painting motifs. From the results of the analysis, 4 Asei bark paintings often use red from betel nut, black from charcoal and white from chalk. Then the images that are often displayed in bark paintings are images of fish, coral (hak balu), fouw, and spears and hooks. The meaning of the symbolic forms shown in the dominance of colors and images on the Asei bark painting is that the Asei people want to tell the geographical conditions of the Asei island which is surrounded by water, Asei Island as a protector for the people, the daily livelihood of the Asei people, the existence of family relationships and the strong togetherness of the Asei people, as well as the community's respect for the ancestors who have protected Asei Island as well as possible.